Factors Affecting Natural Regeneration of Ban Oak (Quercus leucortichophora A. Camus Ex. Bahadur) : I. Seed Fall, Infestation, Losses and Regeneration - Qaisar, K. N.; Mishra, V. K.; Joshi, N. K. (Indian Forester, 1993)
The seedfall observed from Dec.10,1989 to Feb.18,1990 followed, in general, an unimodal pattern assuming maxima on January 9. The sound and infested seeds showed more or less similar pattern with the progress of sampling date. The total seedfall was estimated to be 11.51 seeds/m2 in site-I and 14.76 seeds/m2 in site-II. The average contribution of sound and infested seed to total seedfall was computed to be 34.98 and 65.02 per cent in site-I and 29.01 and 70.99 per cent in site-II respectively. Seed infestation on forest floor as well as tree crown exceeded 50 per cent; the latter was on average relatively lower by 13.18 per cent in site-I and 10.06 per cent in site-II. The per cent seed loss from Feb. to July, 1990 was estimated to be around 73 per cent. The maximum germination took place between July to November. The total number of newly germinated seedlings after one year of seedfall was 0.63/m2 in site-I and 0.36/m2 in site-II.